Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 41586 by MJS last updated on 09/Aug/18

f(x)=(√(−3+(√((x+1)/(x−1)))))  ∫f(x)=?  ∫f^(−1) (x)=?

f(x)=3+x+1x1f(x)=?f1(x)=?

Commented by prof Abdo imad last updated on 10/Aug/18

f(x)=y ⇔x=f^(−1) (y) ⇒(√(−3+(√((x+1)/(x−1))))) =y ⇒  (√((x+1)/(x−1)))  =y^2  +3 ⇒ ((x+1)/(x−1)) =(y^2  +3)^2  ⇒  x+1=x(y^2  +3)^2 −(y^2  +3)^2  ⇒  (1−(y^2 +3)^2 )x=−1−(y^2  +3)^2  ⇒  x=(((y^2  +3)^2  +1)/((y^2  +3)^2 −1)) =1 +(2/((y^2 +3)^2 −1)) ⇒  f^(−1) (x)= 1+(2/((x^2 +3)^2 −1)) ⇒  ∫ f^(−1) (x)dx= x +2 ∫     (dx/((x^2  +3)^2 −1)) +c but  ∫    ((2dx)/((x^2 +3)^2 −1)) = ∫   ((2dx)/((x^2 +4)(x^2 +2)))  = ∫    {(1/(x^2 +2)) −(1/(x^2 +4))}dx=∫  (dx/(x^2 +2)) −∫  (dx/(x^2  +4))  ∫   (dx/(x^2 +2)) =_(x=(√2)t)    ∫ (((√2)dt)/(2(1+t^2 ))) =(1/(√2)) arctan((x/(√2)))  ∫  (dx/(x^2  +4)) =_(x=2t)     ∫  ((2dt)/(4(1+t^2 ))) =(1/2) arctan((t/2))⇒  ∫ f^(−1) (x)dx = x  +(1/(√2)) arctan((x/(√2)))+(1/2)arctan((x/2))+c

f(x)=yx=f1(y)3+x+1x1=yx+1x1=y2+3x+1x1=(y2+3)2x+1=x(y2+3)2(y2+3)2(1(y2+3)2)x=1(y2+3)2x=(y2+3)2+1(y2+3)21=1+2(y2+3)21f1(x)=1+2(x2+3)21f1(x)dx=x+2dx(x2+3)21+cbut2dx(x2+3)21=2dx(x2+4)(x2+2)={1x2+21x2+4}dx=dxx2+2dxx2+4dxx2+2=x=2t2dt2(1+t2)=12arctan(x2)dxx2+4=x=2t2dt4(1+t2)=12arctan(t2)f1(x)dx=x+12arctan(x2)+12arctan(x2)+c

Answered by MJS last updated on 09/Aug/18

∫(√(−3+(√((x+1)/(x−1)))))dx=       [t=(√(−3+(√((x+1)/(x−1))))) → dx=−((8t(t^2 +3))/((t^2 +2)^2 (t^2 +4)^2 ))dt]  =−8∫((t^2 (t^2 +3))/((t^2 +2)^2 (t^2 +4)^2 ))dt=  =−8∫(−(1/(2(t^2 +2)^2 ))+(1/((t^2 +4)^2 ))+(1/(4(t^2 +2)))−(1/(4(t^2 +4))))dt=  =4∫(dt/((t^2 +2)^2 ))−8∫(dt/((t^2 +4)^2 ))−2∫(dt/(t^2 +2))+2∫(dt/(t^2 +4))=       [∫(dx/((x^2 +p)^2 ))=(x/(2p(x^2 +p)))+((√p^3 )/(2p^3 ))arctan ((x(√p))/p)]       [∫(dx/(x^2 +p))=((√p)/p)arctan ((x(√p))/p)]  =(t/(t^2 +2))+((√2)/2)arctan ((t(√2))/2) −(t/(t^2 +4))−(1/2)arctan (t/2) −(√2)arctan ((t(√2))/2) +arctan (t/2)=  =((2t)/((t^2 +2)(t^2 +4)))+(1/2)(arctan (t/2) −(√2)arctan ((t(√2))/2))=  =(√(((√(x+1))−3(√(x−1)))(√((x−1)^3 ))))+(1/2)(arctan((1/2)(√(−3+(√((x+1)/(x−1))))))−(√2)arctan((1/2)(√(−6+2(√((x+1)/(x−1)))))))+C

3+x+1x1dx=[t=3+x+1x1dx=8t(t2+3)(t2+2)2(t2+4)2dt]=8t2(t2+3)(t2+2)2(t2+4)2dt==8(12(t2+2)2+1(t2+4)2+14(t2+2)14(t2+4))dt==4dt(t2+2)28dt(t2+4)22dtt2+2+2dtt2+4=[dx(x2+p)2=x2p(x2+p)+p32p3arctanxpp][dxx2+p=pparctanxpp]=tt2+2+22arctant22tt2+412arctant22arctant22+arctant2==2t(t2+2)(t2+4)+12(arctant22arctant22)==(x+13x1)(x1)3+12(arctan(123+x+1x1)2arctan(126+2x+1x1))+C

Answered by ajfour last updated on 10/Aug/18

(y^2 +3)^2 =1+(2/(x−1))  x=1+(2/((y^2 +3)^2 −1))  f^(−1) (x)=1+(2/((x^2 +3)^2 −1))  I=∫[1+(2/((x^2 +3)^2 −1))]dx  = x+2I_1   I_1 =∫(dx/((x^2 +3)^2 −1)) = ∫(dx/((x^2 +2)(x^2 +4)))     =(1/2)∫(dx/(x^2 +2))−(1/2)∫(dx/(x^2 +4))  hence  ∫f^(−1) (x)dx = x+(1/(√2))tan^(−1) (x/(√2))                                −(1/2)tan^(−1) (x/2)+c .

(y2+3)2=1+2x1x=1+2(y2+3)21f1(x)=1+2(x2+3)21I=[1+2(x2+3)21]dx=x+2I1I1=dx(x2+3)21=dx(x2+2)(x2+4)=12dxx2+212dxx2+4hencef1(x)dx=x+12tan1x212tan1x2+c.

Terms of Service

Privacy Policy

Contact: info@tinkutara.com